Peran Media Sosial dalam Pengembangan Usaha Mikro, Kecil dan Menengah (UMKM) Telur Asin Rahma - Ita Purnama; Nurbaity Raodatun Nadita; Efan Iriadi (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
In the context of MSMEs, social media offers a unique opportunity to expand market reach, build brands, and engage with potential customers at a relatively low cost. With the aim of the study to gain a deeper understanding of how social media can affect various aspects of MSME business. With the results showing that the use of social media has a very important role in the development of Micro, Small, and Medium Enterprises (MSMEs). Social media not only increases the visibility and market reach of MSMEs, but also allows for more intensive interaction with customers and strengthens brand awareness and business image.